Instabilities in Contemporary British Poetry - Robinson, Alan. author. aut Link
XIII, 233 p.
Keywords: The author explores the impact on poetic practice in the 1970s and 1980s of recent theoretical developments, offering a criticism of the work of Seamus Heaney and of poets including Michael Hofmann, reassessing life on Mars and providing retrospective surveys of Fleur Adcock and others.